(untitled) (Journal of Humanitarian and Applied Sciences, 2025)
Understanding the intricate dynamics that control the behavior of viruses like HIV requires the use of models that simulate the spread of epidemic diseases. The objective of this study is to examine how deterministic and stochastic elements affect the epidemic system’s stability, which offers important insights into how to stop the virus’s propagation and enhance treatment approaches. A deterministic model was created to explain the dynamics of the virus’s propagation, emphasizing the system’s stability at particular moments. EE and DFE were the two primary examples that were examined. Numerical results were obtained that demonstrated how the system behaved in various scenarios. To assess how random changes affect epidemiological dynamics, the deterministic model was then transformed into a stochastic model.